2015
DOI: 10.2169/internalmedicine.54.2605
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemic Crisis due to Primary Hyperparathyroidism Occurring Concomitantly with Graves' Disease

Abstract: We herein describe a case of hypercalcemic crisis in a 52-year-old Japanese woman. She suffered from thirst and fatigue for one month. Her serum calcium (a) levels were 19.0 mg/dL, and she was diagnosed with hypercalcemic crisis. Circulating levels of parathyroid and thyroid hormones were elevated. She was diagnosed with primary hyperparathyroidism accompanied by Graves' disease. Thyroparathyroidectomy was performed after circulating levels of Ca and thyroid hormones were normalized. Both of primary hyperparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…[ 2 , 20 ] In addition, some hormones, such as adrenaline and glucocorticoid hormones, are dysregulated under hyperthyroid conditions, thereby contributing to a hypercalcemic state. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 , 20 ] In addition, some hormones, such as adrenaline and glucocorticoid hormones, are dysregulated under hyperthyroid conditions, thereby contributing to a hypercalcemic state. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] To date, only 3 cases of hyperthyroidism complicated with hypercalcemic crisis have been reported. [ 6 8 ] One case was complicated with hyperparathyroidism and the another was with serum calcium of 3.0 mmol/L. [ 6 , 7 ] Endo et al [ 8 ] reported a rare case with serum calcium of 4.1 mmol/L in a patient with hyperthyroidism-associated hypercalcemia.…”
Section: Introductionmentioning
confidence: 99%
“…Th erefore, it is obvious that providing a euthyroid state preoperatively is critical for a safe surgical treatment. Besides, in a case of an hypercalcaemic crisis reported recently by Yokomoto et al (2015), primary hyperparathyroidism and thyrotixicosis was simultaneously present and an operation performed following obtaining an euthyroid and normocalcaemic state resulted in success. In the case presented in this paper, the patient was sent for surgery aft er a euthyroid, normocalcaemic state was provided and successfully treated, and similar to the previously above-stated case.…”
Section: Discussionmentioning
confidence: 96%
“…Hypercalcaemic crisis is a rare complication of primary hyperparathyroidism. Only 1.6-6% of the patients with primary hyperparathyroidism present with hypercalcaemic crisis and the hypercalcaemic crisis is produced generally secondary to other intervening co-morbidities such as pancreatitis, hyperemesis gravidarum and thyrotoxicosis (Yokomoto et al 2015). Association of primary hyperparathyroidism and thyrotoxicosis may facilitate development of hypercalcaemia and this may result in the picture of hypercalcaemic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Severe hypercalcaemia (levels above 3.5 mmol/L) is quite rare 4. There are only a few cases in the literature of hypercalcaemia secondary to hyperthyroidism 5–8. The association of thyroid hormone with calcium levels remains uncertain.…”
Section: Introductionmentioning
confidence: 99%